Determinación de la prevalencia de toxoplasma gondii mediante test de microelisa en gatos domésticos, propietarios y personal de la Clínica Veterinaria Planeta Vida - Toscano Ramos, Lenin Fabricio (2015)
This research aims to determine the prevalence of Toxoplasma gondii by microELISA test in domestic cats, owners and staff of Planeta Vida Veterinary Clinic for correlation of positive cases. Blood samples were collected by venipuncture, draw 2-3 cc, it is passed in vacutainer tubes steeping, we centrifuged for 10 minutes at 1500 rpm separating the cells from plasma or serum, then take 1-3 drops to put in the chamber of adding Test 1 drop of buffer and waited 5-10 minutes for reading. Getting in the investigation of all domestic cats (20 cats) was negative 75% and 25% presented a reaction to IgG; of all owners (20 owners), it was found that 80% were negative for IgG and 20% presented a chronic infection. Additionally the total staff (10 people) it was found that 30% tested positive for IgG and 70% were negative; in 100% three groups tested negative acute infection (IgM). Demostrating that there is no direct correlation between domestic cats and their owners, showing positive cats are not transmitted the disease to their owners.